Study of clinical risk factors for vitreous haemorrhage - Raghuwanshi, Sapna; Raghuwanshi, Shivkumar (International Journal of Medical Research and Review, 2016)
Background: Vitreous haemorrhage is one of the common causes of visual loss and it is due to number of risk factors. This study aims to establish an early etiology of vitreous haemorrhage in our environment which provides proper treatment to help in early absorption and prevention of complications so as to avoid irreversible damage to sight. Methods: A 20 months retrospective review of medical records of patients who admitted in the department of ophthalmology, Gandhi Medical College and associated Hamidia Hospital, Bhopal with vitreous haemorrhage between from April 2010 to December 2011. Demographic data, etiological factors of vitreous haemorrhage and involved eye were amongst the information culled from the records and analysed. Results: Seventy five patients were seen over the period under review out of which 78% they were males. The age range was 16-45 years. Vascular disorders (48%) and trauma accounted for 29.33% of all the causes of vitreous haemorrhage. Conclusion: vascular disorder is a significant cause of vitreous haemorrhage in our environment affecting the all age group and while considering individual aetiological factors the ocular trauma showed highest incidence. The poor presenting visual acuity reflects the severity of causes of vitreous haemorrhage. Awareness needs to be increased to assess the causes and risk factors of vitreous haemorrhage.